Adverse Childhood Experiences and HIV Sexual Risk-Taking Behaviors Among Young Adults in Malawi. Issue 11 (June 2018) - VanderEnde, Kristin; Chiang, Laura; Mercy, James; Shawa, Mary; Hamela, Justin; Maksud, Nankali; Gupta, Sundeep; Wadonda-Kabondo, Nellie; Saul, Janet; Gleckel, Jessie; Kress, Howard; Hillis, Susan
Adverse childhood experiences (ACEs) exhibit a dose–response association with poor health outcomes in adulthood, including HIV. In this analysis, we explored the relationship between ACEs and HIV sexual risk-taking behaviors among young adults in Malawi. We analyzed responses from sexually active 19- to 24-year-old males and females ( n = 610) participating in the Malawi Violence Against Children Survey. We tested the association between respondents' exposure to six ACEs (having experienced emotional, physical, or sexual violence; witnessing intimate partner violence or an attack in the community; one or both parents died) and infrequent condom use in the past year and multiple sexual partners in the past year. We used logistic regression to test the association between ACEs and these sexual risk-taking behaviors. A majority (82%) of respondents reported at least 1 ACE, and 29% reported 3+ ACEs. We found positive unadjusted associations between the number of ACEs (1-2 and 3+ vs. none) and both outcomes. In adjusted models, we found positive associations between the number of ACEs and infrequent condom use (adjusted odds ratio [aOR]: 2.7, 95% confidence interval [CI]: [1.0, 7.8]; aOR: 3.7, CI: [1.3, 11.1]). Among young adults in Malawi, exposure to ACEs is positively associated, in a dose–response fashion, with engaging in some sexual risk-taking behaviors. HIV prevention efforts in Malawi may benefit from prioritizing programs and policies aimed at preventing and responding to violence against children.